Negosiasi Istilah-Istilah Spesifik Budaya Religi Islam dalam Penerjemahan Al-Quran Bahasa Jepang - Asma Haniza; Tatang Hariri; Sajarwa Sajarwa (Vocational College of Diponegoro University, 2026)
The translation of Qur’anic religious texts involved terminological negotiation or the negotiation of religious identity as a translator’s stance in conveying meaning across different languages and cultures. This study aimed to analyze patterns of negotiation in the translation of Islamic religious terms in the Japanese translation of Surah Al-Baqarah of the Qur’an by Saeed Sato, published bye Japan Muslim Association in 2009, as well as to explore the religious, cultural, and theological factors that influenced the emergence of translation negotiation processes. This study employed a qualitative descriptive method with comparative and interpretative approaches. Data collection was conducted through close reading, identification of religiously nuanced linguistic units, and systematic organization into comparative tables. The findings revealed eight patterns of negotiation of Islamic religious terms, including terms related to specific religious practices, morality and ethics, eschatology, religious figures, religious groups, supernatural beings, revelation and enlightenment, and religious activities. Other findings indicated that the primary influencing factors included theological and historical differences, the religious-cultural background or history of the target readers, and moral values.